The perception of brazilian researchers concerning the factors that influence the citation of their articles: A study in the field of sustainability - Jabbour, Charbel JosÃ Chiappetta [UNESP]; de Sousa Jabbour, Ana Beatriz Lopes [UNESP]; de Oliveira, Jorge Henrique Caldeira (Taylor & Francis, 2013)
With growing institutional pressure from the Brazilian government to increase the impact of research that it funds, Brazilian researchers are increasingly interested in discovering factors that affect the citation of their articles. The aim of the present article was to assess the perceptions of Brazilian sustainability researchers to identify factors that influence the impacts of their research. A survey was conducted with researchers in the field of sustainability and 89 questionnaires were completed. All of those researchers have articles or research projects in the field of sustainability (mixing environmental, social and/or economical) recorded in the Scielo or Lattes Curriculum Brazilian databases. Results suggest four factors that may explain the impact of article citations: (1) “prestige of the author and the research network;” (2) “prestige of the means of publication and indexing;” (3) “accessibility and quality characteristics of the article;” and (4) “international nature of communication and scope of the study”. Surprisingly, such factors were not statistically significant in explaining the citations of the participating researchers. These results show the need to consider other factors that can explain the impact of research, discovering the missing links. © 2013 Elsevier Inc.
Keywords: Area of sustainability; Bibliometrics; Brazil; Citation analysis; Impact of research; South America